Replacing 30 Gy in 10 fractions with stereotactic body radiation therapy for bone metastases: A large multi-site single institution experience 2016–2018. (November 2020) - Gillespie, Erin F.; Lapen, Kaitlyn; Wang, Diana G.; Wijetunga, N.; Pastrana, Gerri L.; Kollmeier, Marisa A.; Yamada, Josh; Schmitt, Adam M.; Higginson, Daniel S.; Vaynrub, Max; Santos Martin, Ernesto; Xu, Amy J.; et al.
Highlights: Contemporary trends in radiation technique and fractionation for bone metastases at a large academic center with a specialized metastatic program. Stereotactic body radiation therapy (SBRT) is replacing long-course conventional RT for bone metastases. Complexity of RT is increasing, particularly in the community-based regional clinic setting. Single-fraction conventional RT is preferentially employed at the end of life, but prognostic algorithms are needed to further optimize use. Abstract: Background: Bone metastases cause significant morbidity in patients with cancer, and radiation therapy (RT) is an effective treatment approach. Indications for more complex ablative techniques are emerging. We sought to evaluate RT trends at a large multi-site tertiary cancer center. Methods: Patients who received RT for bone metastases at a single institution (including regional outpatient clinics) from 2016 to 2018 were identified. Patients were grouped by RT regimen: single-fraction conventional RT (8 Gy × 1), 30 Gy in 10 fractions, SBRT, and "other". Multinomial logistic regression was performed to assess trends in regimens over time. Binary logistic regression was performed to evaluate factors associated with receipt of SBRT. Results: Between 2016 and 2018, 5, 952 RT episodes were received by 2, 969 patients with bone metastases. Overall, 76% of episodes were ≤ 5 fractions. The median number of fractions planned for SBRT and non-SBRT episodes was 3 (IQR 3–3) and 5 (IQR 5–10), respectively. Use of SBRT increased from 2016 to 2018 (39% to 53%, p < 0.01) while use of 30 Gy in 10 fractions decreased (26% to 12%, p < 0.01), and 8 Gy × 1 was stable (5.3% to 6.9%, p = 0.28). SBRT was associated with higher performance status (p < 0.01) and non-radiosensitive histology (p < 0.01). Use of SBRT increased in the regional network (19% to 48%, p < 0.01) and at the main center (52% to 59%, p = 0.02), but did not increase within 30 days of death. More patients treated with 8 Gy × 1 than SBRT died within 30 days of treatment (24% vs 3.8%, respectively, p < 0.01). Conclusions: SBRT is replacing 30 Gy in 10 fractions for bone metastases, especially among patients with high performance status and non-radiosensitive histologies. Better prognostic algorithms could further improve patient-centered treatment selection at the end of life.